The correlation between strength and range of motion of the neck muscles and opium smoking in Iran - Massah, Omid; Arab, Amir Masoud; Farhoudian, Ali; Noroozi, Mehdi; Hashemirad, Fahimeh (Frontiers in Psychiatry, 2023)
Objectives: Opium smoking is commonly practiced via traditional and novel routes in Iran. Both smoking methods are practiced in a non-ergonomic position. According to previous studies and our hypothesis, it can be potentially harmful to the cervical spine. Thus, the present study aimed to investigate the relationship between opium smoking and neck range of motion and neck muscle strength. Methods: In this cross-sectional and correlational study, the range of motion and strength of the neck muscles of 120 men with drug use disorder were measured by a CROM goniometer and a hand-held dynamometer. Other data gathering was performed using a demographic questionnaire, the Maudsley Addiction Profile, and the Persian version of Leeds Dependence Questionnaire. The obtained data were analyzed by Shapiro-Wilks test, Pearson’s correlation coefficient and stepwise linear regression. Results: There was no significant correlation between the age of drug use onset and range of motion and muscle strength of the neck; however, the daily duration of opium smoking and the number of years of opium smoking were inversely and significantly correlated with the range of motion and muscle strength of the neck in some directions. Daily opium smoking time for decreasing in neck range of motion and total duration of opium smoking for reduction of neck muscles strength are stronger predictor variables. Conclusion: Opium smoking by traditional routes causes non-ergonomic positions and has a moderate significant correlation with reduced range of motion and neck muscle strength, in Iran.